Analysis of assets structure, net profit margin and current ratio to capital structure - Hertina, Dede; Fahrezi, Irgie Yudha (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of asset structure, net profit margin, and current ratio on the capital structure of telecommunications companies listed on the Indonesia Stock Exchange. The analysis used in this research is multiple regression analysis. The sample used in this study were 6 telecommunications companies listed on the Indonesia Stock Exchange, the data collection period was 2016-2020. This research method uses multiple regression analysis with a significant level of 5%. The results show that simultaneously the asset structure, probability, current ratio has a significant effect on telecommunication companies listed on the IDX for the 2016-2020 period and partially the asset structure has a positive effect on the company's capital structure, the probability value has a positive effect on the capital structure. current ratio has no effect on the structure of telecommunications companies on the IDX for the 2016-2020 period.